Validation of a scale to measure consumers' engagement in voluntary simplistic clothing consumption behaviour in South Africa - Sonnenberg, Nadine Cynthia (University of Pretoria, 2020)
Dissertation (MConsumer Science)--University of Pretoria, 2019.